The Relationship between the Coronavirus conspiracy belief and trust of the people of North Sumatra in the government in combating Covid-19: Hubungan Coronavirus conspiracy belief dengan kepercayaan masyarakat Sumatera Utara terhadap pemerintah dalam penanggulangan Covid-19 - Hani Almira Harahap; Yunita Zahra (Talenta Publisher, 2022)
This study examines the relationship between the Coronavirus conspiracy belief and the North Sumatran people's trust in the Indonesian government in combating the Covid-19 pandemic. This quantitative study used a questionnaire and involved the people of North Sumatra (N = 309) with an accidental sampling technique. The data analysis method is the Pearson product-moment test. The results show that the Coronavirus conspiracy belief and public trust in the government in combating Covid-19 negatively correlate.